2006
DOI: 10.1254/jphs.fmj06002x4
|View full text |Cite
|
Sign up to set email alerts
|

Topics on the Na+/Ca2+ Exchanger: Responses of Na+/Ca2+ Exchanger to Interferon-γ and Nitric Oxide in Cultured Microglia

Abstract: Abstract. The Na + / Ca 2+ exchanger (NCX) plays a role in regulation of intracellular Ca 2+ levels, but little is known about the functional role of NCX in microglia. To clarify the role of NCX in microglia, we studied the responses of NCX to pathological conditions such as interferon-γ or nitric oxide (NO) exposure. Treatment with interferon-γ caused a biphasic increase in NCX activity. The delayed increase in NCX activity was accompanied by increases in the mRNA and protein levels. Pharmacological studies s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 37 publications
(22 reference statements)
0
15
0
Order By: Relevance
“…ASK1 is activated by various stimuli, including calcium influx, ER stress, oxidative stress, lipopolysaccharide (LPS), and receptor-mediated signaling through tumor necrosis factor receptor (TNFR) and Toll-like receptor 4 (TLR4), TLR7, and TLR8 (11,12). Notably, IFN-␥ has been reported to cause Ca 2ϩ influx and ER and oxidative stress in a variety of cell lines (27,28). Activated ASK1 further stimulates the downstream p38 and JNK pathways for driving various cellular responses.…”
Section: Discussionmentioning
confidence: 99%
“…ASK1 is activated by various stimuli, including calcium influx, ER stress, oxidative stress, lipopolysaccharide (LPS), and receptor-mediated signaling through tumor necrosis factor receptor (TNFR) and Toll-like receptor 4 (TLR4), TLR7, and TLR8 (11,12). Notably, IFN-␥ has been reported to cause Ca 2ϩ influx and ER and oxidative stress in a variety of cell lines (27,28). Activated ASK1 further stimulates the downstream p38 and JNK pathways for driving various cellular responses.…”
Section: Discussionmentioning
confidence: 99%
“…This may be attributed to phosphorylation of NCX, because PKC can phosphorylate NCX, and most, but not all, studies have reported PKC-mediated increase in NCX activity (Vigne et al, 1988;Iwamoto et al, 1996b). The involvement of PKC and tyrosine kinase in controlling NCX activity in microglia has previously been reported by Matsuda et al (2006). PI3K is also involved in reverse mode of NCX activity, as observed in neonatal cardiomyocytes (McDowell et al, 2004).…”
Section: The Signal Cascade Of B 1 Receptor Activationmentioning
confidence: 92%
“…Another interesting observation was the involvement of NCX operating in reverse mode leading to Ca 2ϩ influx. Although the physiological function of NCX is assumed to be Ca 2ϩ extrusion, Matsuda et al (2006) provide evidence that Ca 2ϩ uptake via NCX operating in reverse mode may play a role for microglial function under pathological conditions. The signaling cascade of BK and its coupling to NCX might be quite distinct in microglia compared with other cell types.…”
Section: Distinct Mechanisms Of Microglial Migration Induced By Bk Anmentioning
confidence: 96%
See 1 more Smart Citation
“…2,3) Recently, a potent and selective NCX enzyme inhibitor, 2-[4-[(2,5)-difluoro-phenyl]methoxy]-5-ethoxyaniline (SEA0400) has been developed, 4) and has been reported to provide protection in models of cerebral ischemia and reperfusion injury after ischemia. 5,6) However, the effect of NCX on epilepsy has not been reported.…”
mentioning
confidence: 99%